READABILITY OF TEXTS FOR THE TENTH GRADE STUDENTS OF SMA NEGERI 3 MEDAN - Irma Andriyani Nasution; Amrin Saragih (Universitas Negeri Medan, 2016)
This research was quantitatively and qualitatively conducted to analyze the readability of texts for the tenth grade students of SMA Negeri 3 Medan. The sources of the data were seven texts taken from students’ textbook entitled Bahasa Inggris. The texts in the second semester are written both in Recount and Narrative genres. The data were analyzed using Flesch Reading Ease Formula which is focused on the average sentence length and the average number of the syllables per words. The findings of this research show that the texts were grouped into five levels, they are Standard, Easy, Difficult, Very Easy and Fairly Easy. The average readability score for all texts is 70 which implies that the texts are in Standard level and are therefore compatible with the theory of Flesch which indicates that the texts are readable. However, in line with Flesch’ theory, the tenth grade students should be given a text which category belongs to Fairly Difficult and in relation to that, it is concluded that the texts in the textbook are readable yet they are inappropriate to be used for the tenth grade students.